2006
DOI: 10.1159/000091619
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Characteristics of Patients Presenting with Biochemical Progression after Radical Retropubic Prostatectomy for Pathologically Organ-Confined Prostate Cancer

Abstract: Introduction: To identify risk factors for biochemical failure after radical prostatectomy (RP) in men with pathologically organ-confined (OC) prostate cancer (PCa). Materials and Methods: Clinical and pathological features of 350 consecutive patients with pathologically OC PCa treated only with RP and bilateral pelvic lymphadenectomy were analyzed, retrospectively, to identify predictor parameters of prostate-specific antigen (PSA) failure (PSA ≧0.4 ng/ml). The median follow-up was 58.6 months (range: 3.9–183… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Although some authors saw no independent prognostic factor for bNED (no biochemical evidence of disease), in other studies the positive apical margin with pT2 carcinomas was identified as being an independent prognostic factor [5,11] . There are no randomized studies comparing 'wait and see' and adjuvant radiotherapy.…”
Section: Adjuvant Radiotherapy For Patients With Pt2 Tumors and Positmentioning
confidence: 89%
See 2 more Smart Citations
“…Although some authors saw no independent prognostic factor for bNED (no biochemical evidence of disease), in other studies the positive apical margin with pT2 carcinomas was identified as being an independent prognostic factor [5,11] . There are no randomized studies comparing 'wait and see' and adjuvant radiotherapy.…”
Section: Adjuvant Radiotherapy For Patients With Pt2 Tumors and Positmentioning
confidence: 89%
“…While for tumor stage pT2 the meaning of the positive margins is controversial, it is indisputable that in tumor stage pT3 positive margins represent an independent risk for biochemical progression [5][6][7] . According to this positive margin, it seems reasonable to suppose that the remaining microscopic tumor is usually obvious at the height of the anastomosis region, but also in the resection bed of the prostate.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure of RP in these patients is not easily understood, and has been reported to occur in 5-23% of the patients. [4][5][6] In patients who achieve PSA nadir of 0.01 ng/mL post-surgery, as in our series, it is even harder to explain failure of RP. Although an erroneous pathological classification may, in terms of either the cancer penetrating the PCa (pT3) or an anatomically incorrect dissection plane (unrevealed positive margin), which left behind microscopic amounts of PCa and then subsequently progressed, explain some cases but not the majority.…”
Section: Discussionmentioning
confidence: 52%
“…[1,2] Although the percentage of patients with pathologically organ-confined tumors has substantially increased [3] , 4-32% of these men will eventually relapse following radical prostatectomy (RP). [4][5][6] Multivariate analyses have reportedly revealed that the pathological tumor grade (Gleason score) and preoperative serum PSA are highly predictive of outcome following RP for pathologically localized PCa. [7] More recently, it has been reported than even men with high grade Gleason scores of 8-10 have long-term outcomes similar to those men with more favorable disease characteristics when the disease is pathologically organ confined.…”
Section: Introductionmentioning
confidence: 99%